Peripheral Nerve Stimulation for Treatment of Headaches: An Evidence-Based Review - Steven Zhou; Nasir Hussain; Alaa Abd-Elsayed; Racha Boulos; Mohammed Hakim; Mayank Gupta; Tristan Weaver (Biomedicines, 2021)
Headaches are one of the most common medical complaints worldwide, and treatment is often made difficult because of misclassification. Peripheral nerve stimulation has emerged as a novel treatment for the treatment of intractable headaches in recent years. While high-quality evidence does exist regarding its use, efficacy is generally limited to specific nerves and headache types. While much research remains to bring this technology to the mainstream, clinicians are increasingly able to provide safe yet efficacious pain control.